Squamous Cell Skin Carcinoma in Systemic Lupus Erythematosus: Case Report and Literature Review - S. V. Topolyanskaya (SINAPS LLC, 2020)
The case report of squamous cell skin carcinoma diagnosed in a patient with systemic lupus erythematosus 26 years after the onset of rheumatic disease is presented. The features of this case included the absence of skin manifestations of systemic lupus erythematosus, the occurrence of a tumor at the site of ulcers and trophic disorders on the leg, a long period (6 years) from the onset of a ulcerative defect on the leg to the diagnosis of skin cancer (despite multiple biopsies and consultations of various specialists), as well as the occurrence of a cytokine release syndrome, which directly led to the death of the patient after the first use of the immune checkpoint inhibitors. Possible causes of skin cancer in patients with systemic lupus erythematosus, as well as the features of the cytokine release syndrome after immunotherapy for oncological diseases, are discussed.